Expectations towards Global Organisational Leaders - Haromszeki, Łukasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
This article analyses issues about organisational leaders who have an impact on behaviour internationally. According to leadership categorisation theory, social identity and leadership theory, the expectations of employees are the result of many different processes which come out during the process of socialisation. People have some ideas about what constitutes a successful leader, which they compare with different managers’ behaviour and image created in, for example, international organisations. The article presents ideas from and results of different international studies presented in the literature about this issue as well as my own pilot studies on expectations towards global organisational leaders which exist on the Web. The article presents circumstances of formed leadership relationships on a global scale. In conducting my research I sought to determine the significance of socio-cultural changes in the process of creating a model of expectations towards global organisational leaders, and also to illustrate the similarities and differences brought about by the context of the occurrence of a leadership relationship.